ARENA AIRSOFT GUN DI KABUPATEN TANAH LAUT - Asshidiqi, Hasby; Hadinata, Irwan Yudha (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Pelaihari sub-district is one of the sub-districts in Tanah Laut Regency which is the center of government and offices for the regional government. Pelaihari sub-district is the most developed sub-district in Tanah Laut Regency. The tourism sector in Pelaihari District is very well developed, people outside Pelaihari make Pelaihari a tourist destination during holidays or weekends. Airsoft guns are replicas of firearms that are now used as sports equipment. Airsoft gun hobbyists realize the battlefield by shooting between teams. Strategizing or just getting an adrenaline rush is the goal of the airsoft gun game. Airsoft gun has now become a recreational sport which means that airsoft gun can be used as a tourist destination. Although classified as an extreme sport, airsoft gun can be a family-friendly tourist destination if it is equipped with good facilities and uses the right scenario.